ANALYSIS OF FUEL UTILIZATION EFFICIENCY INDICES IN ENERGY SYSTEMS - V. N. Nagornov; V. V. Kravchenko (Наука и техника, 2007)
The paper considers main indices of fuel utilization efficiency in energy systems. The basic emphasis is made on investigations of the existing fuel utilization efficiency indices in the Belarusian energy system. The investigation is resulted in a coefficient of useful fuel utilization, which allows to inter-relate the efficiency of electrical and heat energy generation with the Belenergo energy saving special-purpose index. The useful fuel utilization coefficient can be calculated both with and without taking into consideration the annual actual saving of conditional fuel in the Belenergo system that makes it possible to determine the influence of the Belenergo energy saving measures on the useful fuel utilization coefficient in the Belarusian energy system.